2014
DOI: 10.1063/1.4892924
|View full text |Cite
|
Sign up to set email alerts
|

Properties of magnetic tunnel junctions with a MgO/CoFeB/Ta/CoFeB/MgO recording structure down to junction diameter of 11 nm

Abstract: We investigate properties of perpendicular anisotropy magnetic tunnel junctions (MTJs) with a recording structure of MgO/CoFeB/Ta/CoFeB/MgO down to junction diameter (D) of 11 nm from 56 nm. Thermal stability factor (Δ) of MTJ with the structure starts to decrease at D = 30 nm. D dependence of Δ agrees well with that expected from magnetic properties of blanket film taking into account the change in demagnetizing factors of MTJs. Intrinsic critical current (IC0) reduces with decrease of D in the entire investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
171
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(182 citation statements)
references
References 24 publications
9
171
0
2
Order By: Relevance
“…In our 50 × 150nm superparamagnetic tunnel junctions, we identified that the switching occurs through nucleation and propagation of a magnetic domain, probably seeded by fluctuations in a subset of grains within it 31 (supplementary information S3). By contrast, recent experiments on perpendicular magnetic anisotropy (PMA) magnetic tunnel junctions have shown that aggressively scaled devices (diameters smaller than 35nm) switch at the scale of the whole volume 34 . Therefore, in the context of random number generators, extreme scaling of the nanodevices appears as providential, as smaller volumes and areas are directly linked to a lower magnetization stability of the free magnet 40 , increasing random bit generation speed exponentially.…”
Section: Scaling Capabilities Of the Random Number Generators In mentioning
confidence: 95%
See 2 more Smart Citations
“…In our 50 × 150nm superparamagnetic tunnel junctions, we identified that the switching occurs through nucleation and propagation of a magnetic domain, probably seeded by fluctuations in a subset of grains within it 31 (supplementary information S3). By contrast, recent experiments on perpendicular magnetic anisotropy (PMA) magnetic tunnel junctions have shown that aggressively scaled devices (diameters smaller than 35nm) switch at the scale of the whole volume 34 . Therefore, in the context of random number generators, extreme scaling of the nanodevices appears as providential, as smaller volumes and areas are directly linked to a lower magnetization stability of the free magnet 40 , increasing random bit generation speed exponentially.…”
Section: Scaling Capabilities Of the Random Number Generators In mentioning
confidence: 95%
“…We see that the resistance follows two-state fluctuations analogous to a random telegraph signal. The mean frequency of fluctuations is strongly related to the shape and material properties of the junction 34 . Fig.…”
Section: Exploiting the Stochastic Behavior Of Superparamagnetic mentioning
confidence: 99%
See 1 more Smart Citation
“…K eff can often be improved by introducing a second CoFeB/MgO interface in more complicated MgO/CoFeB/Ta/CoFeB/MgO structures [4]. Nevertheless, it has been shown that even the optimized MTJ structure is unstable for dimensions below 30 nm [5]. Novel materials with strong magnetocrystalline or strain-induced PMA are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetostatic interaction between layers is largely offset by the exchange and not included here. The objective of this design is to maximize the switching efficiency ξ-the existing figure of merit: [8][9][10] …”
Section: Simulation Modelmentioning
confidence: 99%